Auditory processing disorder in perisylvian syndrome - Boscariol, Mirela; Garcia, Vera Lucia [UNESP]; Guimaraes, Catarina Abraao; Montenegro, Maria Augusta; Vasconcelos Hage, Simone Rocha; Cendes, Fernando; Guerreiro, Marilisa Mantovani (Elsevier B.V., 2010)
We hypothesized that the processing of auditory information by the perisylvian polymicrogyric cortex may be different from the normal cortex. To characterize the auditory processing in bilateral perisylvian syndrome, we examined ten patients with perisylvian polymicrogyria (Group 1) and seven control children (Group 11). Group I was composed by four children with bilateral perisylvian polymicrogyria and six children with bilateral posterior perisylvian polymicrogyria. The evaluation included neurological and neuroimaging investigation, intellectual quotient and audiological assessment (audiometry and behavior auditory tests). The results revealed a statistically significant difference between the groups in the behavioral auditory tests, Such as, digits dichotic test, nonverbal dichotic test (specifically in right attention), and random gap detection/random gap detection expanded tests. Our data showed abnormalities in the auditory processing of children with perisylvian polymicrogyria, suggesting that perisylvian polymicrogyric cortex is functionally abnormal. We also found a correlation between the severity of our auditory findings and the extent of the cortical abnormality. (C) 2009 Elsevier B.V. All rights reserved.
Keywords: Auditory cortex; Auditory perception; Dichotic listening; Perisylvian syndrome; Polymicrogyria